PELABUHAN SEBAGAI PENGHUBUNG JALAN LAUT DAN DARAT Studi Kasus Pelabuhan Banjarmasin dan Batu Licin, Kalimantan Selatan - Andi Nuralang (Naditira Widya, 2006)
Banjarmasin and Batulicin harbor are two ports, which have flourished since the past and still actively operating until today. Both harbors are administratively located in SouthÂ Kalimantan; Batulicin on its east periphery accommodating bay activities while Banjarmasin on its west is beneficial for river activities. Each harbor carries out its own management and business without ever intruding one another. The prime function of both harbors is the outer gate of South Kalimantan.